Psychological Distress and Embitterment in Young Transgender, Homosexual, and Heterosexual Individuals in an Islamic Country - Tofighi, Moujan; Linden, Michael (British Journal of Healthcare and Medical Research, 2024)
Background: Sexual and gender minorities may experience prejudice and discrimination, leading to a reduction in their quality of life (QoL) and harming their mental health. Independent of discrimination, psychological impairment can result from individual-level factors, such as primary mental disorders. By assessing not only general QoL but also specific emotions such as embitterment, which is associated with the experience of injustice, it is possible to differentiate the impairment of QoL resulting from discrimination-caused reactions. The hypothesis was that sexual and gender minorities score higher on embitterment and have a lower QoL than heterosexuals. There should be differences between homosexual and transgender people in a society that punishes homosexual individuals while accepting transgender people such as Iran. Method: 27 female-to-male transgender individuals from a private clinic, 17 homo(bi)sexuals and 18 heterosexual participants in Iran completed the “WHOQOL_BREF”, a measure of the quality of life, and the “Post-Traumatic Embitterment DisorderSelf-ratingg scale DScalee)”. The participants were between 18 and 25 years old. Results: There was a significant negative correlation between QoL and embitterment level. The WHOQOL_BREF and the PTED scores did not differ between the groups. Single items on WHOQOL_BREF revealed that transgender individauls had more problems with physical appearance and self-satisfaction. Conclusion: This study didn't support the hypothesis of poor quality of life or increased embitterment among young sexual and gender minorities in Iran. Transgender participants were dissatisfied with their body appearance. Even in the presence of discrimination discrimination, this does not necessarily lead to mental health impairment in this population.